Characteristics of Mangrove Forest in Anak Setatah Village Riau Province for Community-Based Tourism Village Development - Yoswaty, Dessy; Warningsih, Trisla; Batubara, Ummi Mardiah; Wahyuni, Inka (Jurnal Perikanan dan Kelautan, 2022)
The community in Anak Setatah Village has made efforts to conserve and rehabilitate mangrove forest ecosystems that have been damaged by abrasion, land conversion and mangrove forest encroachment. The TEGAS Community Group (Pokmas) established a mangrove nursery and planting business independently. The existence of mangrove forests that grow well can provide opportunities for the development of tourist villages. The aim of the research is to identify the characteristics of mangrove forests in Anak Setatah Village, Riau Province for the development of community-based tourism villages. The research uses survey methods, there are 3 (three) research locations, namely Station I of the mangrove tourism area (Dusun Karet settlement), Station II of the mangrove tourism area (mangrove forest conservation) and Station III of the mangrove tourism area (Dusun Karet beach). Research activities have been carried out in October 2021-January 2022. The results showed that the density of mangroves growing in the mangrove forest ecosystem of Anak Setatah Village, namely Station I, was 1122 ind/ha; Station II is 1799 ind/ha and Station III is 1289 ind/ha. Mangrove density at Station I and Station III is classified as medium category, at Station II is classified as very dense category. the results of the identification of mangrove vegetation in Station I obtained 2 species of mangrove (Avicennia alba and A.marina); Station II obtained 4 mangrove species (Rhizophora apiculata, R.mucronata, A.alba and A.marina); and Station III obtained 2 species of mangrove (A.alba and A.marina). The results showed that the mangrove forest ecosystem in Anak Setatah Village had an average IKW value, namely the appropriate category (S2) with an average IKW value at Station I (61.84%); Very suitable category (S1) with an average IKW score at Station II (84.21%) and suitable category (S2) with an average IKW score at Station III (65.79%). Overall the three research stations have the characteristics of mangrove forests that grow well and the community plays an active role in preserving the mangrove forest so that it provides opportunities to be developed as a tourist village.